Dynamic process modelling of the HPS2 solar thermal molten salt parabolic trough test facility - Temlett, Robert (Department of Mechanical Engineering, 2019)
In recent years power generation from renewable energy has grown substantially both in South Africa and around the world. This growth is set to continue as there is more pressure to reduce the burning of fossil fuels. However, renewable energy power generation suffers from unpredictability, which causes problems when it comes to managing power grids. Concentrated Solar Power (CSP) plants offer a practical solution to store power in the form of thermal energy storage (TES). Thus, the plant can run when there is no solar energy available, leading to a more stable power supply. Unfortunately, CSP plants cost more than other renewables such as photovoltaic and wind power. Thus, there is a need for research into how to bring down the cost of CSP plants. One of the most proven types of CSP is the parabolic trough plant. The most recent innovation is to try and use molten salt as the heat transfer fluid which would reduce the cost of the plant. However, this new technology has not been implemented on a full scale CSP plant and little testing has been done to prove the technology. The HPS2 is a test facility aimed at testing the use of molten salt as a heat transfer fluid (HTF). This test facility, located in Evora Portugal, is being developed by an international consortium led by the German DLR institute of Solar Research. It is one of the first test facilities of its kind where experiments will be conducted to demonstrate the validity of using molten salt as a HTF and a storage medium in a parabolic trough CSP plant. The HPS2 test facility is not yet operational and there is a need for a dynamic thermofluid process model to better understand and predict both its steady state and transient operational behaviour. This dissertation reports on the development of such a dynamic thermofluid process model and the results obtained from it. The process model developed primarily focuses on the steam cycle with the TES incorporated into the model. The physical geometry of each of the components are employed to construct discretized elements for which the conservation of mass, energy, and momentum are applied in a one-dimensional network approach. The economizer and evaporator combined has a helical coil geometry and uses molten salt as a heat transfer fluid, which is unique. Thus, correlations had to be adjusted for the flow characteristics found in the economizer/evaporator. Results from the steady state simulations of the steam cycle show that the molten salt mass flowrate through the steam generation system will have to be reduced from the initially expected value to meet operational requirements. Results of the dynamic simulations show that the test facility will be able to produce a constant power supply despite transient solar conditions and highlights key dynamic responses for operators to be aware of.